(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The aim was to find out the effect of selected yogasanas on fasting blood sugar and postprandial blood sugar among Annamalai University Men Staff. The investigator administered a brief questionnaire among men staff on their health status and presence of diabetics. The questionnaire was administered among 200 Men staff. Based on the survey, Men Staff undergoing for diabetics treatment were identified. From such Men Staff, randomly selected 40 as subjects for this study. The age group of the subjects was between 45 to 55 years. They were preliminarily assessed of their blood sugar through standard tests and medical reports of them were verified. The selected subjects were assigned into two different groups based on their mean random blood sugar level. Equated groups design was used with twenty subjects in each group, namely control group, experimental group.